If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -1(3x + -6) = 2x + -1(4 + -8) Reorder the terms: 3 + -1(-6 + 3x) = 2x + -1(4 + -8) 3 + (-6 * -1 + 3x * -1) = 2x + -1(4 + -8) 3 + (6 + -3x) = 2x + -1(4 + -8) Combine like terms: 3 + 6 = 9 9 + -3x = 2x + -1(4 + -8) Combine like terms: 4 + -8 = -4 9 + -3x = 2x + -1(-4) Multiply -1 * -4 9 + -3x = 2x + 4 Reorder the terms: 9 + -3x = 4 + 2x Solving 9 + -3x = 4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 9 + -3x + -2x = 4 + 2x + -2x Combine like terms: -3x + -2x = -5x 9 + -5x = 4 + 2x + -2x Combine like terms: 2x + -2x = 0 9 + -5x = 4 + 0 9 + -5x = 4 Add '-9' to each side of the equation. 9 + -9 + -5x = 4 + -9 Combine like terms: 9 + -9 = 0 0 + -5x = 4 + -9 -5x = 4 + -9 Combine like terms: 4 + -9 = -5 -5x = -5 Divide each side by '-5'. x = 1 Simplifying x = 1
| 3x+3-9=5x+6-7x | | 4(x-3)=3(-x+2) | | 4.7m=-32.9 | | (30+5x)=(15+10x) | | 132=6x-72 | | 121=6x-72 | | -x-3=2(x+3) | | 0.7x=-1.3 | | 5(-4+7x)=85 | | 2(3n+2)=7(8n+3)+7 | | 0.4(a-24)=0.8a | | 7(-6x+1)=-77 | | 3(2x+4)=3x-6 | | -3y-4(6y+2)=y-9 | | 0.8y-0.3y=4.5 | | 5x-4=-4x+23 | | x+(x+1)=25 | | -2x+6=34+5x | | -3(2x+1)=27 | | 3x+6=2x+16 | | 1+5x=-4x+64 | | 4-2(x-2)=3 | | 2x^2-4x-6=1 | | 7x+x-9=55 | | 2x+23=71 | | 2x+4=3x-11 | | 55=7x+x-9 | | 23(78)+(67)89= | | 5(4x-2)+9=(8x+7) | | 4(x-3)=-12 | | (9x-5)2=25 | | 6x+8=18x |